Pharmacological significance of shatavari; The Queen of herbs. - Akansha Singh; B. Sinha (International Journal of Phytomedicine, 2014)
Shatavari (A. racemosus) has been used since ages by the rural people as a galactagogue. The herb is a source of phytochemicals like steroidal saponins, sapogenins, flavonoids (kaempferol, quercetin, and rutin), and poly phenols (secondary metabolites that have high pharmacological importance). These active principals gives medicinal value to the plant as anti-ulcerogenic, anti-oxytocic, anti-tussive, anti-diabetic, immunostimulants, cardioprotective, anti-cancerous, anti-hepatotoxic, anti-bacterial, anti-diarrheal, anti-aging, anti-depressant, anti-lithiatic, and anti-candidal activities. The review has been written in an attempt to enlist the detailed aspects of pharmacological significance of shatavari with the aim to provide a direction for further clinical research to promote safe and effective herbal treatments to cure a number of diseases.